Rethinking the evaluation of educational intervention effectiveness through Activity Theory: a mobile app example - Ilishkina, Daria I. (Frontiers in Education, 2025)
IntroductionThere has been a growing shift toward practically oriented research that focuses on analyzing and improving educational interventions rather than merely validating them. However, such research is often prone to theoretical bias and result fragmentation, as it tends to prioritize certain aspects of an intervention without clear justification, losing a systemic perspective.MethodsBy applying Activity Theory within a mixed-method approach, this study introduces a holistic framework for evaluating educational interventions as interconnected systems, offering a more comprehensive foundation for research and practice. As a demonstration, this study examines the effectiveness of the second version of the mobile application “Ace Yourself,” designed to develop soft skills in higher education.Results and discussionThis approach enables an exploration of how the application aligns with students’ needs, considers the learning context, roles, and competing activities, and ultimately contributes to learning outcomes. Viewing education as a system rather than isolating individual elements reveals new insights and contradictions through their interconnections and lays the foundation for future decision-making.